Recent Developments in Nanotechnology and Immunotherapy for the Diagnosis and Treatment of Pancreatic Cancer - Sindhi, Komal; Kanugo, Abhishek (Current Pharmaceutical Biotechnology, 2025)
Pancreatic cancer kills millions of people worldwide each year and is one of the most prevalent causes of mortality that requires prompt therapy. A large number of people suffering from pancreatic cancer are detected at an advanced stage, with incurable and drug-resistant tumor, hence the overall survival rate of pancreatic cancer is less. The advance phase of this cancer is generated because of expression of the cancer-causing gene, inactivation of the tumor-suppressing gene, and deregulation of molecules in different cellular signalling pathways. The prompt diagnosis through the biomarkers significantly evades the progress and accelerates the survival rates. The overexpression of Mesothelin, Urokinase plasminogen activator, IGFR, Epidermal growth factor receptor, Plectin-1, Mucin-1 and Zinc transporter 4 were recognized in the diagnosis of pancreatic cancer. Nanotechnology has led to the development of nanocarriers-based formulations (lipid, polymer, inorganic, carbon based and advanced nanocarriers) which overcome the hurdles of conventional therapy, chemotherapy and radiotherapy which causes toxicity to adjacent healthy tissues. The biocompatibility, toxicity and large-scale manufacturing are the hurdles associated with the nanocarriers-based approaches. Currently, Immunotherapy-based techniques emerged as an efficient therapeutic alternative for the prevention of cancer. Immunological checkpoint targeting techniques have demonstrated significant efficacy in human cancers. Recent advancements in checkpoint inhibitors, adoptive T cell therapies, and cancer vaccines have shown potential in overcoming the immune evasion mechanisms of pancreatic cancer cells. Combining these immunotherapeutic approaches with nanocarriers holds great promise in enhancing the antitumor response and improving patient survival.
Keywords: nanoparticles